Kelimpahan dan Keanekragaman Spesies Echinodermata sebagai Indikator Fungsi Ekologi Lamun di Perairan Pesisir Lombok Timur - Lalu Raftha Patech; Abdul Syukur; Didik Santoso (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
Seagrasses are plants in the marine environment and have a vital function for the survival of organisms. This study aims to describe the indicators of the seagrass ecological function of the diversity of echinoderms species. The research method used is the method of line and square transects. Data analysis uses analysis of abundance (Ki), diversity (H ') Shannon Wieners, Morisita Dispersion Index, and Jaccard Index. The results showed that the highest seagrass species found at Lungkak beach were 8 species and the lowest was in the Mangrove Poton of 6 species. Furthermore, the number of species of Echinoderms found was 14 species, and the species with the highest abundance was Diadema setosum with a value of 1.21 Individual / m2, and the species that had the lowest abundance was Holothuria scabra) with a value of 0.01 Individual / m2. Meanwhile, the location with the highest value H 'is in Gili Kere with a value of 1.76, and the location with the lowest value of H' is in Lungkak with a value of 1.01. Furthermore, the value of the Seagrass Morisita Dispersion Index and Echinoderms in the study area had a uniform and grouped pattern. The quantitative and qualitative values obtained are a form of seagrass ecological contribution to the sustainability of Echinoderms in the study location. Therefore, the results of this study can be a scientific basis for the importance of the existence of seagrass beds, especially for the sustainability of marine life such as species of Echinoderms.